English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

solve for the value of m..

3m - 4/6 = 2m + 3/2

it's kinda difficult,, pls help me.. tnx..

2007-07-09 00:27:10 · 14 answers · asked by ToLiTz 1 in Science & Mathematics Mathematics

14 answers

3m - 4/6 = 2m + 3/2
3m -2m = 3/2 + 4/6
m(3-2) = (9 + 4) / 6
m = 13/6
simplify
m = 2 and 1/6

2007-07-09 00:36:47 · answer #1 · answered by gostob2 3 · 0 0

3m - 4/6 = 2m +3/2
take "2m" from both sides of the equals sign to make:
m - 4/6 = 3/2
add 4/6 to both sides of the equals sign:
m - 4/6 + 4/6 = 3/2 + 4/6
m = 3/2 + 4/6
make the fractions have a common denominator
m = 9/6 + 4/6
m = 13/6

2007-07-09 07:48:21 · answer #2 · answered by Anonymous · 0 0

Try to simplify the equation by rewriting the equation without fractions.
Multiply both sides by the LCD of 4/6 and 3/2 which is 6
6*(3m - 4/6) =6*( 2m + 3/2)
18m - 4 = 12m +9
18m-12m = 9 + 4
6m = 13
m = 13/6

2007-07-09 07:36:38 · answer #3 · answered by olens 2 · 0 0

3m - 4/6 = 2m + 3/2
bring terms of m on LHS & numerals on RHS
3m-2m=3/2+4/6
m=3/2+2/3
m=(3*3+2*2)/2*3
m=13/6=2 1/6

2007-07-09 07:39:07 · answer #4 · answered by Jain 4 · 0 0

3m - 4/6 = 2m + 3/2

Move every term which has an m to the left hand side, and everything else to the right hand side.

3m - 2m = (4/6) + (3/2)

m = (4/6) + (9/6)

m = 13/6

2007-07-09 07:36:19 · answer #5 · answered by Puggy 7 · 0 0

3m - 4/6 = 2m + 3/2

3m - 2m = 3/2 + 4/6

m = 9/6 + 4/6

m = 13/6 or 2 1/6

2007-07-09 07:36:10 · answer #6 · answered by SheTigger2 4 · 0 0

3m -4/6 = 2m +3/2
Move -4/6 to RHS and 2m to LHS

3m -2m = 3/2 + 4/6

Now, bring both fractions to same base.

Multiply both numerator and denominator of 3/2 by 3 = 9/6

Note that multiplying both numerator and denominator by same number will not change the value of the fraction as it will retain same "ratio".

Hence,
m = 9/6 + 4/6
m = 13/6

m = 2.166

2007-07-09 07:46:00 · answer #7 · answered by Vivek 2 · 0 0

3m - 4/6 = 2m + 3/2

Shifting the 'm' terms to the LHS and the constant terms to the RHS......
3m - 2m = 4/6 + 3/2

Simplifying the equation......
m = 4/6 + 9/6
m = 13/6
m = 2 and 1/6

2007-07-09 07:35:23 · answer #8 · answered by Anonymous · 0 1

subtract 2m from both sides
3m-2m-4/6=2m-2m+3/2

m-2/3=3/2
add 2/3 to both sides
m=3/2+2/3
m=13/6

2007-07-09 07:50:05 · answer #9 · answered by iyiogrenci 6 · 0 0

13/6

2007-07-09 20:45:01 · answer #10 · answered by Anonymous · 0 0

fedest.com, questions and answers